THE SIGNIFICANCE OF TONI MORRISON’S VOICE IN EXPANDING AFRICAN AMERICAN LITERTURE - Rajabova Dildora Rakhimovna (Western European Studies, 2025)
This paper examines the significance of Toni Morrison’s narrative voice in expanding the scope and direction of African American literature. It argues that Morrison not only enriches the tradition through her representation of Black memory, identity, and community, but also reshapes its literary possibilities through innovative narrative forms. Drawing on close textual analysis of selected novels, including “Beloved”, “Song of Solomon”, and “The Bluest Eye” the study explores how Morrison reclaims silenced histories, integrates oral storytelling traditions, and constructs a language that reflects the emotional and cultural realities of African American life. Nowadays, her works still continues to influence contemporary writers and remains essential for understanding the evolving landscape of Black literary expression.
Keywords: Toni Morrison; African American literature; cultural memory